Collaborative enhancement of thermal diffusivities and mechanical properties of Csf-Cu/Mg composites via introducing Cu coating with different thicknesses - Yuan Ma; Lingjun Guo; Jiancheng Wang; Baolin Chen; Lehua Qi; Hejun Li (Journal of Magnesium and Alloys)
Mg alloy matrix composites reinforced with short carbon fibers (Csf/Mg) are considered as potential candidates for integrated structural-functional electronic parts that satisfy the requirements of lightweight, excellent mechanical properties, and heat dissipation. However, the different characteristics of Csf and Mg alloy make the interface a critical issue affecting the synergistic improvement of thermal and mechanical properties of the composites. Here, Cu coating with different thicknesses is introduced to modify the Csf/Mg interface, so as to simultaneously enhance the thermal and mechanical performances, which can combine the advantages of coating modification and matrix alloying. Results reveal that thermal diffusivity (TD) of 3-Csf-Cu/Mg composites is as high as 22.12 mm2/s and an enhancement of 52.97% is achieved compared with Csf/Mg composites, as well as 16.3% enhancement of ultimate compressive strength (UCS) in the longitudinal direction, 8.84% improvement of UCS in the transverse direction, and 53.08% increasement of ultimate tensile strength (UTS). Such improvement can be ascribed to the formation of intermetallic compounds. The formation of intermetallic compounds can not only effectively alleviate the lattice distortion of the matrix and decrease interfacial thermal resistance, but also bear the loads. Our work is of great significance for designing Csf/Mg composites with integrated structure and function.